The optimization design and test of camfull-row-pick-up seeding mechanism. Issue 1 (December 2020) - Li, Liangliang; Niu, Wenjing; Qi, Zhengdong; Chen, Jie; Guodang, Lian; Haiyang, Tang
Abstract: The mechanism components and working principle were analysed, and then cam mechanism was simplified into slider-crank mechanism to facilitate the establishment of kinematic model. The target optimization function for structural parameters was solved out via mathematical model combined with the transplanting requirements, then a computer-aided analysis program based on Visual Basic 6.0 was developed for optimizing structural parameters of the mechanism. According to the optimized structural parameters, the three-dimensional model of mechanism was established and the automatic seedling pick-up test-bed was conducted. The analysis of kinematic simulation and the test of prototype test were carried out. The success rate of picking up seedlings reaches 95% and efficiency of taking seedling is 3600 strains per hour. The cam full-row-pick-up seedling mechanism is feasible and effective to achieve the operation requirements of whole-row-pick-up seedling.